The Effect Of Financial Distress, Audit Fee, and Management Change On Auditor Switching - Deliana, Deliana; Lubis, Rizal Ikromi; Rahman, Abdul; Surianti, Meily; Zakaria, Maheran (Universitas Pendidikan Indonesia, 2025)
The main purpose of this research is to examine the influence of financial distress, audit fees, and management changes on auditor switching among consumer non-cyclical corporations registered on the IDX over the years 2020–2024. The research method employs secondary data obtained from the Indonesia Stock Exchange, with a sample of 46 companies over five years (230 observations). Data were collected using documentation techniques and analyzed using logistic regression with SPSS version 29. The findings reveal that financial distress does not influence auditor switching, while audit fee and management turnover significantly affect auditor switching. These indicates suggest cost considerations and leadership dynamics play a stronger role than financial conditions in driving companies to switch auditors. The results highlight the importance of governance and contractual factors over financial pressure in auditor-client relationships. The theoretical implication of this study contributes to agency theory by emphasizing the role of audit fees and management changes in auditor switching behavior. Practically, the findings provide insights for auditors and regulators to strengthen audit quality and anticipate factors influencing auditor changes. The novelty of this work is reflected in the emphasis focus on consumer non-cyclical companies in Indonesia with an extended observation period of 2020–2024, providing a broader understanding of auditor switching in the Indonesian business context.